PERBEDAAN KUALITAS HIDUP LANSIA HIPERTENSI DAN TIDAK HIPERTENSI DI DESA BOKOHARJO WILAYAH KERJA PUSKESMAS PRAMBANAN SLEMAN : Rumini Widyasningrum , Antok Nurwidi Antara, Murgi Handari - Rumini Widyasningrum; Antok Nurwidi; Murgi Handari (Jurnal Kesehatan Hesti Wira Sakti, 2023)
ABSTRACT Background : Hypertension is one of the focuses of health attention in the world, especially in developing countries and is a cause of high morbidity and mortality throughout the world. The increase in the number of hypertension sufferers, especially in the elderly with all the biopsychosocial problems caused, has resulted in a decrease in the quality of life of sufferers Research objective: To find out the differences in the quality of life of hypertensive elderly and non-hypertensive elderly in Bokoharjo Village Prambanan Health Center, Sleman Yogyakarta Methods: This type of research is quantitative using a descriptive comparative design with a cross sectional design. The research population for elderly hypertension and non-hypertension in Bokoharjo Village, Prambanan Health Center, totaling 1293 people, was taken using the Proportional Random Sampling technique, with 102 samples consisting of 2 groups of hypertensive elderly, 51 people and 51 elderly people who were not hypertensive. The data collection tool used the World Health Organization Quality Of Life (WHOQOL) –100 questionnaire. Data analysis used an independent sample t-test Results: The results showed that the elderly with hypertension had a quality of life score of 75.02 ± 4.41 and the elderly without hypertension had a quality of life score of 80.43 ± 6.33 with a p value of 0.000 (p <0.05). Conclusion: There is a difference between the quality of life of hypertensive elderly and non-hypertensive elderly in Bokoharjo Village Prambanan Health Center, Sleman Yogyakarta keywords: Quality of Life, Elderly, Hypertension